2021
DOI: 10.1159/000517975
|View full text |Cite
|
Sign up to set email alerts
|

Synbindin Downregulation Participates in Slit Diaphragm Dysfunction

Abstract: <b><i>Introduction:</i></b> Synbindin, originally identified as a neuronal cytoplasmic molecule, was found in glomeruli. The cDNA subtractive hybridization technique showed the mRNA expression of synbindin in glomeruli was downregulated in puromycin aminonucleoside (PAN) nephropathy, a mimic of minimal-change nephrotic syndrome. <b><i>Methods:</i></b> The expression of synbindin in podocytes was analyzed in normal rats and 2 types of rat nephrotic models, anti-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[19][20][21]46 Ivanov et al recently demonstrated that Trappc4 is an early marker for detecting podocyte injury and participates in slit diaphragm dysfunction in puromycin aminonucleoside nephropathy. 18 However, only a few studies have investigated the regulatory role of Trappc4 in nephrolithiasis. In this study, Trappc4 protein expression was lower in the crystal group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21]46 Ivanov et al recently demonstrated that Trappc4 is an early marker for detecting podocyte injury and participates in slit diaphragm dysfunction in puromycin aminonucleoside nephropathy. 18 However, only a few studies have investigated the regulatory role of Trappc4 in nephrolithiasis. In this study, Trappc4 protein expression was lower in the crystal group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that Trappc4, one of the five candidate proteins, regulates cellular apoptosis and is involved in kidney injury. 18,20,21 In addition, Trappc4 strongly interacted with lycopene (binding energy is −6.9 kcal mol −1 ), indicating that lycopene maintains a strong stable binding state with Trappc4. Therefore, Trappc4 should be investigated further in future studies.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation